2006
DOI: 10.1063/1.2364163
|View full text |Cite
|
Sign up to set email alerts
|

Bias dependent inversion of tunneling magnetoresistance in Fe∕GaAs∕Fe tunnel junctions

Abstract: We investigated spin dependent transport through Fe/GaAs/Fe tunnel junctions.The tunneling magnetoresistance effect (TMR) was probed for different types of Fe/GaAs interfaces. For interfaces cleaned by hydrogen plasma the TMR effect is increased and observable at room temperature. If an epitaxial Fe/GaAs(001) interface is involved, the tunnel junction exhibits a bias dependent inversion of the TMR effect. This is a first experimental signature for band structure effects at a Fe/GaAs interface and relevant for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 27 publications
3
52
0
Order By: Relevance
“…Some theories predict very large tunnel magnetoresistance: the electronic-structure of the zincblende crystal makes 'coherent tunnelling' across the Fe/GaAs(001) interface possible 16 . Moser et al fabricated Fe/GaAs/Fe(001) devices and find magnetoresistance around 6 % at 4.2 K, which reverses sign with increasing bias 17 : a result somewhat short of the 1000s of % change predicted. However, more recent theoretical work by Autès et al has demonstrated that, due to the strong spin-orbit coupling in GaAs, saturation of the magnetoresistance is reached with increasing GaAs thickness, and a limited magnetoresistance (in the range as low as 30-50 %) results 18 .…”
Section: Introductionmentioning
confidence: 98%
“…Some theories predict very large tunnel magnetoresistance: the electronic-structure of the zincblende crystal makes 'coherent tunnelling' across the Fe/GaAs(001) interface possible 16 . Moser et al fabricated Fe/GaAs/Fe(001) devices and find magnetoresistance around 6 % at 4.2 K, which reverses sign with increasing bias 17 : a result somewhat short of the 1000s of % change predicted. However, more recent theoretical work by Autès et al has demonstrated that, due to the strong spin-orbit coupling in GaAs, saturation of the magnetoresistance is reached with increasing GaAs thickness, and a limited magnetoresistance (in the range as low as 30-50 %) results 18 .…”
Section: Introductionmentioning
confidence: 98%
“…The 13 nm thick epitaxial iron layer was grown on an 8 nm thin GaAs (001) barrier by transferring the freshly grown GaAs heterojunction from the molecular beam epitaxy chamber to a magnetron sputtering system without breaking the ultrahigh vacuum (UHV). The quality of the interface of a sample from the same wafer was checked by high-resolution transmission electron microscopy [5]. The Fe layer was covered by 50 nm cobalt and 100 nm gold which serves as back contact.…”
mentioning
confidence: 99%
“…The barrier heights can depend on the preparation technics [6] and were assumed to be 0.75 eV on each side, which was found for the Fe/GaAs interface [7]. Hence the GaAs layer constitutes a nearly rectangular barrier allowing, e.g., observation of the TMR [5,7]. In total, four batches of samples which differ in the preparation of the Au layer (with and without H + -plasma etching step, see e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, establishing a method to keep the MR ratio high, e.g., the use of highly spin-polarized ferromagnetic electrodes, is essential. In fact, such an example has recently been reported by Kasai et al 12 Finally, let us discuss the reason why only low MR ratios have been observed in the GaAs-and ZnSe-based MTJs, 15,16,30 as opposed to the CIGS-based MTJ. To this end, we calculated MR ratios of Fe/GaAs/Fe and Fe/ZnSe/Fe MTJs using supercells with 17 barrier layers and 3 Fe layers on both sides of the barrier.…”
mentioning
confidence: 81%